Interdisciplinary care in disorders/differences of sex development (DSD): The psychosocial component of the DSD—Translational research network. Issue 2 (2nd June 2017) - Sandberg, David E.; Gardner, Melissa; Callens, Nina; Mazur, Tom; ,
Abstract : Scientific discovery and clinical management strategies for Disorders/Differences of Sex Development (DSD) have advanced in recent years. The 2006 Consensus Statement on Management of Intersex Disorders stated that a mental health component to care is integral to promote positive adaptation, yet the parameters of this element have not been described. The objective of this paper is threefold: to describe the psychosocial screening protocol adopted by the clinical centers of the DSD‐Translational Research Network; to summarize psychosocial data collected at 1 of the 10 network sites; and to suggest how systematic behavioral health screenings can be employed to tailor care in DSD that results in better health and quality of life outcomes. Steps taken in developing the largely "noncategorical" screening protocol are described. These preliminary findings suggest that DSD, as one category of pediatric chronic conditions, is not associated with marked disturbances of psychosocial adaptation, either for the family or the child; however, screening frequently uncovered "risk factors" for individual families or patients that can potentially be addressed in the context of ongoing clinical care. Administration of the DSD‐TRN psychosocial screening protocol was demonstrated to be feasible in the context of interdisciplinary team care and was acceptable to families on a longitudinal basis. The ultimate value of systematic screening will be demonstrated through a tailoring of psychosocial, medical and surgical services, based on this information that enhances the quality of patient and family‐centered care and subsequent outcomes.